2018
DOI: 10.1038/s41598-018-33959-x
|View full text |Cite
|
Sign up to set email alerts
|

A systems biology network analysis of nutri(epi)genomic changes in endothelial cells exposed to epicatechin metabolites

Abstract: Although vasculo-protective effects of flavan-3-ols are widely accepted today, their impact on endothelial cell functions and molecular mechanisms of action involved is not completely understood. The aim of this study was to characterize the potential endothelium-protective effects of circulating epicatechin metabolites and to define underlying mechanisms of action by an integrated systems biology approach. Reduced leukocyte rolling over vascular endothelium was observed following epicatechin supplementation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 76 publications
6
41
0
Order By: Relevance
“…Literature lacks data about the effect of Passiflora on miRNA expression. However, it has been suggested that plant food bioactives can modulate the expression of miRNA [85,86]. Among the miRNA identified from bioinformatic analysis as potentially involved in the post-transcriptional regulation of identified differentially expressed genes by PS juice consumption, we can list miRNA-16, -26, and -124. miRNA-16 has shown to play a role in inflammation [87] and hypertension [88], whereas miRNA-124 mediates anti-inflammatory effects and is involved in neuroprotective mechanisms [89].…”
Section: Discussionmentioning
confidence: 99%
“…Literature lacks data about the effect of Passiflora on miRNA expression. However, it has been suggested that plant food bioactives can modulate the expression of miRNA [85,86]. Among the miRNA identified from bioinformatic analysis as potentially involved in the post-transcriptional regulation of identified differentially expressed genes by PS juice consumption, we can list miRNA-16, -26, and -124. miRNA-16 has shown to play a role in inflammation [87] and hypertension [88], whereas miRNA-124 mediates anti-inflammatory effects and is involved in neuroprotective mechanisms [89].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms by which dietary flavan-3-ols mediate these effects on vascular health include nitric oxide–dependent arterial function (51, 52), anti-inflammatory effects (53), and effects on glucose metabolism, β-cell function, and inhibition of glucose transporters (54–57). However, early mechanistic studies did not consider the absorption, distribution, metabolism, and excretion of the flavan-3-ols.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to pharmacological drugs (for example glucocorticoids (GC)) which can trigger drastic expression changes of GC-responsive genes (typically, log 2 fold > 1), many bioactive phytochemicals rather induce moderate transcriptional changes (typically log 2 fold > 0,4) of multiple genes converging on the same pathway [44][45][46]. Genes differentially expressed (DEG) by Echinaforce® treatment were enriched for IPA canonical pathways related to innate immune responses including interferon signaling, interferon regulatory factor (IRF) activation and the role of pattern recognition receptors, among others ( Figure 1B-C and Supplementary table 2).…”
Section: Echinaforce® Treatment Activates Innate Immunity Genes and Pmentioning
confidence: 99%
“…A total of 1,875 CpG sites was found differentially methylated (FDR < 0.1) with a methylation difference of at least 5%. Typically, DNA methylation changes after short (24-72h) exposure to phytochemicals and nutrients are much smaller than cancer associated DNA methylation changes in oncogenes or tumor suppressor genes which accumulate for many years in response to the microenvironment [46,68,69]. However, similar DMR effects sizes and cutoff (<5%) were found to be biologically meaningful in various disease etiologies [40,70,71].…”
Section: Echinaforce® Treatment Elicits Epigenetic Changes In Innate mentioning
confidence: 99%